(untitled) (Palíndromo, 2026)
This article examines sixteenth-century Reformation aesthetics through the problem of the visibility of the divine and argues that the Protestant Reformation, by dismantling the medieval confidence in the image as a mediator of the sacred, produced historical and sensory conditions that anticipate what modernity would later call the sublime. Beginning with Luther’s critique of the superstitious veneration of images and Calvin’s systematic refusal to accept any attempt to circumscribe God through the gaze, the text analyzes how the depletion of images, whether through the Lutheran refinement of sacred representation or the iconoclastic impulse of Calvinist communities, established new aesthetic modes of relating to the invisible. Drawing on Edmund Burke, we suggest that categories such as awe, grandeur and infinity find parallels in the Reformation experience of the sacred. Finally, we connect these transformations to modern thought on the unrepresentable, especially in Lyotard, to show how the Reformation inaugurates a sensibility in which the divine no longer manifests itself through the image but through an absence that exceeds the eye. What theology expresses as the impossibility of representing God thus reappears in modern philosophy as the aesthetic experience of the sublime.